Sejarah sosial intelektual Islam di Indonesia - Hasbullah, Moeflich, 1965- (Bandung : Pustaka Setia, 2012)
Social history of Islamic thoughts in Indonesia.
Includes bibliographical references (p. 373-391).
Keywords: Islam -- Indonesia -- History; Islam -- Social aspects -- Indonesia